"It's Totally Destroyed Our Life": Exploring the Pathways and Mechanisms Between Precarious Employment and Health and Well-being Among Immigrant Men and Women in Toronto. (January 2018) - Premji, Stephanie
Precarious employment is rapidly growing, but qualitative data on pathways to and mechanisms for health and well-being is lacking. This article describes the cumulative and intersecting micro-level pathways and mechanisms between precarious employment and health among immigrant men and women in Toronto. It draws on semi-structured interviews conducted in 2014 with 15 women and 12 men from 11 countries of origin. The article describes how precarious employment, conceptualized by workers as encompassing powerlessness, economic insecurity, work for multiple employers, nonstandard and unpredictable schedules, hazardous working conditions, and lack of benefits and protections, negatively impacts workers' physical and mental health as well as that of their spouses or partners and children. It documents pathways to health and well-being, including stress, material and social deprivation, and exposure to hazards, as well as commuting difficulties and childcare challenges. Throughout, gender and migration are shown to influence experiences of work and health. The findings draw attention to dimensions of precarity and pathways to health that are not always highlighted in research and discourse on precarious employment and provide valuable insights into the vicious circle of precarious employment and health.